Study protocol for a randomised controlled trial on the use of intraoperative ultrasound-guided laparoscopic ovarian cystectomy (UGLOC) as a method of fertility preservation in the management of benign ovarian cysts - Srdjan Saso; Sadaf Ghaem-Maghami; Jan Yvan Jos Verbakel; Benjamin P Jones; Joseph Yazbek; Mona El-Bahrawy; Lorraine S Kasaven (BMJ Open)
Introduction The lifetime risk of women undergoing surgery for the presence of benign ovarian pathology in the UK is 5%–10%. Despite minimally invasive surgical techniques, evidence suggests a number of healthy ovarian follicles and tissues are resected intraoperatively, resulting in subsequent decline of ovarian reserve. As such, there is an increasing demand for the implementation of fertility preservation surgery (FPS). This study will evaluate the effect on ovarian reserve following two different surgical interventions for the management of benign ovarian cysts.Methods and analysis We will conduct a two-armed randomised controlled trial comparing laparoscopic ovarian cystectomy, considered gold standard treatment as per the Royal College of Obstetricians and Gynaecologists (RCOG) Green Top guidelines for the management of benign ovarian cysts, with ultrasound-guided laparoscopic ovarian cystectomy (UGLOC), a novel method of FPS. The study commencement date was October 2021, with a completion date aimed for October 2024. The primary outcome will be the difference in anti-Müllerian hormone (AMH) (pmol/L) and antral follicle count (AFC) measured 3 and 6 months postoperatively from the preoperative baseline. Secondary outcomes include assessment of various surgical and histopathological findings, including duration of hospital stay (days), duration of surgery (minutes), presence of intraoperative cyst rupture (yes/no), presence of ovarian tissue within the resected specimen (yes/no) and the grade of follicles excised within the specimen (grade 0–4). We aim to randomise 94 patients over 3 years to achieve power of 80% at an alpha level of 0.05.Ethics and dissemination Findings will be published in peer-reviewed journals and presented at national and international conferences and scientific meetings. The Chelsea NHS Research and Ethics Committee have awarded ethical approval of the study (21/LO/036).Trial registration number NCT05032846.